If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + -4x = -3 + -2x + y Reorder the terms: -4x + 2y = -3 + -2x + y Solving -4x + 2y = -3 + -2x + y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -4x + 2x + 2y = -3 + -2x + 2x + y Combine like terms: -4x + 2x = -2x -2x + 2y = -3 + -2x + 2x + y Combine like terms: -2x + 2x = 0 -2x + 2y = -3 + 0 + y -2x + 2y = -3 + y Add '-2y' to each side of the equation. -2x + 2y + -2y = -3 + y + -2y Combine like terms: 2y + -2y = 0 -2x + 0 = -3 + y + -2y -2x = -3 + y + -2y Combine like terms: y + -2y = -1y -2x = -3 + -1y Divide each side by '-2'. x = 1.5 + 0.5y Simplifying x = 1.5 + 0.5y
| 8x-5=63 | | (3.2+1)-(0.6*7)= | | Logx(256)=2 | | 5+2y=(-1) | | -14x+2y=-2 | | -3(2a-3)=3(a-6) | | h+4=2h-19 | | z=3*x-y | | y=0.95x | | 9.2-x=7.3 | | -7x+y=-1 | | 3x-11=x-5 | | -3(2x-3)=3(x-6) | | 4x+3=2(2x+2)-2x | | y=0.75(4)x | | 4=-0.5x^2+46 | | 42=12+3p | | 31(2c+4)=2(c+6)+c | | 7[2e-1]-3=6+6e | | 32=7(n+7)+5(5n+3) | | Y+2=.6(x+4) | | 42=2.333333x | | 6x+34x=7 | | 10p-3=2[12+4p]-7 | | 800=2x+3x+10x | | 9g=3[-4+5g] | | 500=2x+8x | | Y=-.6x-1 | | 3j+10=-30 | | .13x+x=141 | | 4[3+c]+c=c+4 | | 400=2x+6x |